REKLAMASI DAN RESTORASI EKOLOGI KAWASAN TANJUNG API – API PROVINSI SUMATERA SELATAN - Reflis, Reflis (Jurnal AGRISEP, 2017)
Damage to mangrove forests should be stopped by holding conservation activities, even restore to reorganize. These activities not only protect and preserve the species as well as providing a tourist attraction (ecotourism) but should also serve to improve the socio-economic conditions of the surrounding community in the context of sustainable development. This paper is to explain the problems of environmental degradation, especially the large-scale exploitation of mangrove forests in the region of Tanjung Api-Api Reclamation, Banyuasin regency of South Sumatra province. The method used is a review of research papers and reports on Reclamation area of Tanjung Api-Api and management of Special Economic Zones (SEZ). Reclamation activities Tanjung Api-Api is basically not recommended because it lowers the quality of mangrove Environment and Watershed Musi, but the public interest by taking into account all the benefits that this can be continued reclamation of origin according to applicable regulations and pay attention to aspects related impact and benefits. Damage to ecosystems due to reclamation Tanjung Api-Api quite alarming, therefore it is necessary to the recovery through the restoration of mangrove forest and watershed restoration Musi integrated. Ecological restoration is expected to restore the function and role of the mangrove ecosystem and watershed Musi.